(untitled) (An Naba, 2020)
The Book of Ta’lim Al-Muta’allim is a book compiled and composed by Syekh Al-Zarnujy, and translated by Aliy As’ad, is a book and reference as well as guidance for a claimant of knowledge in order to gain useful knowledge for himself in particular and society in general.In this analysis, the data that has been collected and arranged, is then sorted out words that have translation problems in the translation of the Ta’lim Al-muta’allim using a dictionary. To find out the words that are considered meaningful Qawl, Kalam, and their different derivative forms of words and to find out the relationship of these words, the Semantic science approach is used, precisely by using the Translation Problems.After doing research, it is found that the Translation Problems of the Qawl, Kalam, and its derivatives, namely: the words Qawl, Kalam, and their derivatives when juxtaposed with God means to speak, juxtaposed with the Prophet / Apostle means to say, and if juxtaposed with Man means to say or speak. Issues that are problematic in translation are caused by differences in the scope of meaning, differences in use, differences in the use of forms, differences in the field of meaning, and differences in social and cultural culture.